The Effect of Work Engagement and Job Satisfaction on Organizational Commitments at PT. Karya Sakti Sejahtera - Hana Meilinda; Agung Wahyu Handaru; Dewi Susita (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2022)
The purpose of this study was to determine the effect of Work Engagement and Job Satisfaction on Organizational Commitment to the employees of PT. Karya Sakti Sejahtera, which is a company engaged in the construction sector in Indonesia. The population of this study was 103 people, and the sampling method used was saturated sampling, so the number of samples in this study was also 103 people. This research uses multiple linear regression analysis methods in analyzing research data. The results showed that both Work Engagement and Job Satisfaction had a significant positive effect on Organizational Commitment, both partially and simultaneously. This implies that the higher the employee's job involvement and job satisfaction, the higher the employee's organizational commitment to the company.